각종 임상검체에서 분리된 세균의 균종과 항생제 감수성의 추세 - 조용현 (연세대학교 보건대학원, 1985)
[한글] 근년 원내외의 감염양상이 다양해지고 항생제 내균성의 출현으로 인해 병원균의 균종별 추세와 항생제 감수성을 아는 것은 환자치료의 기초가 된다고 하겠다. 이 연구에서는 1980년 1월부터 1984년 12월 사이에 경희의료원에서 분리 동정된 균종들의 추세와 항생제 감수성을 분석하여 다음과 같은 결과를 얻었다. 1. 그람양성 구균 10,594주, 그람양성 간균 7주 및 그람 음성간균 22,340주가 분리되었다. 각 연도별 분리 균주수에는 별 차이가 없었다. 2. 검체별 분리수로는 요에서 9,993주로 가장 많았고 농에서 9,702주, 객담과 기관지 검체에서 6,568주, 혈액에서 1,618주등의 순으로 분리되었으며 균종별 분리수는 E. coli가 5,462주로 가장 많았고 S. aureus 4,866주, P. aeruginosa 3,913주 Klebsiella sp. 2, 866주의 순이었다. Proteus sp.는 시험기간중 2배 정도 증가했고 P.aeruginosa가 100주 이상 증가했다. 반면 Salmonella와 Shigella의 분리수가 1984년에 크게 감소하였다. 3. 대부분의 균종이 여름철에 다소 높은 분리비율을 보였으나, S. typhi는 8∼9월, 12∼2월에 다소 높은 분리 비율을 보였다. S. pneumoneae는 봄철 환절기때 다소 높은 분리 비율을 보였다. 4. S. aureus는 penicillin G에 내성인 균주가 90% 이상이었고 cephalothin과 cloxacillin에 감수성인 균주가 감소하였다. S. fecalis는 penicillin G에 90% 이상이 감수성 이었으나 cepalothin을 제외한 나머지 항생제에는 거의 내성이었다. 그러나 S. pneumoneae 와 β-hemolytic Streptococcus는 내성의 문제가 없음이 확인되었다. Salmonella를 제외한 Enterobacteriaceae와 포도당 비발효 그람음성 간균의 ampicillin, kanamycin 혹은 carbenicillin에 대한 내성 균주의 증가는 현저 하였으나, amikacin, cepalothin gentamici n에는 비교적 높은 감수성율을 보였다. Salmonella는 95%에서 100%의 균주가 감수성으로서 내성문제는 없었다. 이 연구에서 Proteus sp. 와 P.aeruginosa 의 증가와 Salmonella와 Shigella의 분리 비율이 감소됨이 분명하고, 대부분의 균종이 여름철에 다소 높은 분리 비율을 보이며, S.typhi는 8∼9월과 12∼2월에 두 번 분리 빈도가 높으며 종래부터 사용하던 항생제에 대해 내성인 균주가 현저히 증가되어 가고 있어서 큰 문제점으로 대두되었다는 결론을 얻었다. Trends of bacterial species isolated from various clinical specimens and the antimicrobial susceptibility Yonghyun Cho Department of Public Health Graduate School of Health Science and Management (Directed by Associate Professor Yunsop Chong, Ph.D.) The changes in the pattern of bacterial infection in hopitals as well as in community and the increase of infections due to resistant organisms have been reported to be a serious problem. Therefore it became essential to monitor the trends of bacterial species isolated and their susceptibility to antimicrobial agents to be able to treat the patients effectively. In this study an analysis was made on the trends of bacterial species and antimicrobial susceptibility of the isolates at Kyung-hee Medical Center from January 1980 to December 1984. The following results were obtained. 1. The number of isolates of gram-positive cocci were 10,594, gram-positive bacilli 7 and gram-negative bacilli 22,340. There was not great difference in the annual number of isolates. 2. The number of isolation by specimen showed it was greatest from urine 9,993, and other major sources were pus 9,702, sputum and bronchial specimens 6,568 and blood 1,618. Most frequently isolated species of vacteria were E. coli 5,462, and other major isolates include S. aureus 4,866, P. aeruginosa 3,913, and Klebsiella sp. 2,866. Number of Isolates of Proteus sp. increased twofold and increase of as much as 100 isolates of P. aeruginosa were noted when the data of 1983 and 1984 were compared. Sharp decrease was noted in the Salmonella and Shiegella isolation during the study period. 3. Most if the species of bacteria were isolated slightly more frequently in summer, while the isolation of S. typhi was somewhat more frequent from August to September and from December to Februaty. Isolation of S. pneumoniae was more frequent in spring, i.e., at the turn of the season. 4. More than 90% of S. aureus isolates were resistant to penicillin G. and decrease of susceptible strains to cephalothin and cloxacillin were noted during the study period. Over 90% of S. fecalis were susceptible to penicillin G but most of them were resistant to other agents with the exception to cephalothin. S. pneumoniae and β-hemolytic Streptococcus presented no resistance problem. Enterobacteriaceae with the exception of Salmonella, and glucose nonfermenting gram-negative bacilli showed remarkabl increase of resistant strains to ampicillin, kanamycin or carbenicillin. amikacin, cephalothin, and gentamicin remained highly active. To the antimicrobial agents tested 95% to 100% of Salmonella isolates were susceptible indicating no resistance problem. It is concluded from this study that isolation of Proteus and P. aeruginosa is increasing while Salmonella and Shgella is decreasing, that in most of the species the isolation is somewhat more frequent in summer while the isolation of S. typhi is more frequent from August to September and from December to Februaty, and that increasing proportion of isolates are resistant to commonly used antimicrobial agents posing serious problem in the treatment of infection. [영문] The changes in the pattern of bacterial infection in hopitals as well as in community and the increase of infections due to resistant organisms have been reported to be a serious problem. Therefore it became essential to monitor the trends of bacterial species isolated and their susceptibility to antimicrobial agents to be able to treat the patients effectively. In this study an analysis was made on the trends of bacterial species and antimicrobial susceptibility of the isolates at Kyung-hee Medical Center from January 1980 to December 1984. The following results were obtained. 1. The number of isolates of gram-positive cocci were 10,594, gram-positive bacilli 7 and gram-negative bacilli 22,340. There was not great difference in the annual number of isolates. 2. The number of isolation by specimen showed it was greatest from urine 9,993, and other major sources were pus 9,702, sputum and bronchial specimens 6,568 and blood 1,618. Most frequently isolated species of vacteria were E. coli 5,462, and other major isolates include S. aureus 4,866, P. aeruginosa 3,913, and Klebsiella sp. 2,866. Number of Isolates of Proteus sp. increased twofold and increase of as much as 100 isolates of P. aeruginosa were noted when the data of 1983 and 1984 were compared. Sharp decrease was noted in the Salmonella and Shiegella isolation during the study period. 3. Most if the species of bacteria were isolated slightly more frequently in summer, while the isolation of S. typhi was somewhat more frequent from August to September and from December to Februaty. Isolation of S. pneumoniae was more frequent in spring, i.e., at the turn of the season. 4. More than 90% of S. aureus isolates were resistant to penicillin G. and decrease of susceptible strains to cephalothin and cloxacillin were noted during the study period. Over 90% of S. fecalis were susceptible to penicillin G but most of them were resistant to other agents with the exception to cephalothin. S. pneumoniae and β-hemolytic Streptococcus presented no resistance problem. Enterobacteriaceae with the exception of Salmonella, and glucose nonfermenting gram-negative bacilli showed remarkabl increase of resistant strains to ampicillin, kanamycin or carbenicillin. amikacin, cephalothin, and gentamicin remained highly active. To the antimicrobial agents tested 95% to 100% of Salmonella isolates were susceptible indicating no resistance problem. It is concluded from this study that isolation of Proteus and P. aeruginosa is increasing while Salmonella and Shgella is decreasing, that in most of the species the isolation is somewhat more frequent in summer while the isolation of S. typhi is more frequent from August to September and from December to Februaty, and that increasing proportion of isolates are resistant to commonly used antimicrobial agents posing serious problem in the treatment of infection.
보건학과/석사